The Mediating Effect of Psychological Contract and Job Satisfaction on the Relationship between Leadership and Job Performance: A Proposed Framework - Algathia, Salem Ali; Mohamed, Rosmah; Choy Leong , Yee; Abdullah, Abdul Rashid (Advances in Social Sciences Research Journal, 2022)
Today, more than ever, achieving Job Performance is one of the most challenging objectives for companies. The main objective of this paper is to investigate the role of Psychological Contracts and Job Satisfaction as mediators in leadership and Job performance relationships in the Saudi hospital sector. Moreover, the direct effect of leadership practice on Job performance. Simultaneously, the literature background of variables of study under the psychological contract theory would be discussed to propose the research model. The study depends on the secondary resource, the nature of the study, therefore, is exploratory, and the analysis relies on critical content analysis and theming procedure to construct its findings. The study found that both psychological contracts and job satisfaction have a mediating role in the relationship between leadership and job performance.